Gender Awareness in Households in Oeltua Village,Taebenu District, Kupang Regency - Arif, Farida M; Handayani, Suci Lestari; Idris, Idris; Arifin, Amri Adha; Wuhdin, Sulaiman Mustafa; Kiwang, Amir S; Abdussamad, Zulkhaedir; Nurdin, Nurdin; Uduk, Lusia D; Dawu, Leopold Meikiano Triangga (UNIVERSITAS MUHAMMADIYAH MATARAM, 2024)
This community service aims to raise gender awareness within households in Oeltua Village, Taebenu District, Kupang Regency. The Women's and Children's Protection Agency (P3A) of East Nusa Tenggara Province reported a high incidence of violence against women, mostly domestic violence. Community service was conducted by lecturers and students of the Faculty of Social and Political Sciences, Muhammadiyah University of Kupang, through lectures and counseling methods. The results showed an increased understanding among participants about the importance of the father's role in child-rearing and equitable distribution of household tasks. The involvement of fathers in child-rearing not only alleviates the burden on women but also positively impacts child development. Education and campaigns about gender equality and women's empowerment are needed to reduce domestic violence cases and achieve gender role balance within families.